Becoming Urban: New Zealand towns in the 1850s - Schrader, Ben (Architectural History Aotearoa, 2012)
During the 1850s the first inland towns were founded at Greytown and Masterton. They signalled a new direction in Pākehā settlement, a movement from coastal edge port "cities" to secondary towns in the (North Island) interior. It was from these centres that colonisation proceeded apace. These new towns followed the pattern of New Zealand urbanism established in the 1840s: low-density development with houses and buildings scattered over a wide domain. Could they then really be called towns? Architecturally, the built environment of all towns might be best described as utilitarian and frontier-like. But the decade is notable for the first expressions of a grander, civic architecture, best shown in the construction of public buildings, some of which are examined here. Were these New Zealand's first urban buildings?